Transformation of hardening to softening behaviors induced by Sb substitution in CuO-doped KNN-based piezoceramics. Issue 10 (July 2019) - Liao, You; Wang, Dongmei; Wang, Hua; Wang, Tao; Zheng, Qiaoji; Yang, Jiahui; Kwok, K.W.; Lin, Dunmin
Abstract: Pb-free piezoceramics of K0.5 Na0.5 Nb1- x Sb x O3  + 1 mol% CuO are synthesized via a solid-state reaction. Furthermore, the transformation of hardening to softening behaviors induced by Sb substitution is exhibited and the corresponding microscopic mechanism is proposed. The CuO-doped K0.5 Na0.5 NbO3 ceramic without adding Sb exhibits extremely hardening characteristics (i.e., ultrahigh Q m of ∼2426, low tanδ of 0.32%, and pinched ferroelectric hysteresis loop) due to the formation of defect combinations ( ( Cu Nb ''' − V o ) ' and ( V o − Cu Nb ''' − V o ) ). Whereas, the addition of Sb dramatically reduces the levels of defect combinations, leading to obviously softening properties ( d 33  > 210 pC N −1, k p  > 40%, low Q m, and normal single P-E hysteresis loop). Our results indicate that the decrease of defect combinations with Sb addition should be responsible for the hardening-softening transformation of piezoelectricity and ferroelectricity in CuO-doped K0.5 Na0.5 Nb1- x Sb x O3 piezoceramics.